Pengaruh Flash Sale, Online Customer Review, Dan Gratis Ongkos Kirim, Terhadap Keputusan Pembelian Produk Umkm Erigo Pada Marketplace Shopee (Studi Kasus Konsumen Erigo Kota Malang) - Prasetya, Effendi Handi; Asiyah, Siti; Rachmadi, Kartika Rose (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to examine and analyze the influence of flash sales, online customer reviews, and free shipping on the purchase decision of ERIGO UMKM products on the Shopee marketplace. The research approach utilized is quantitative, employing a survey method and data collection through questionnaires. The population in this study consists of ERIGO consumers in Malang City who have made purchases on Shopee. The sample size was determined using the Ferdinand formula, resulting in 75 respondents selected through purposive sampling technique.Data analysis method includes validity test, reliability test, normality test, multicollinearity test, heteroskedasticity test, multiple regression analysis, F-test, t-test, and coefficient of determination. The results indicate that simultaneously, flash sales, online customer reviews, and free shipping have a positive and significant impact on purchase decisions. Partially, flash sales and online customer reviews have a positive and significant influence, while free shipping has a positive but not significant effect on the purchase decision of ERIGO products on Shopee. The contribution of independent variables to the dependent variable is 39,3%, while the remaining portion is influenced by other variables outside the research model. Keywords : Flash Sale, Online Customer Review, Gratis Ongkos Kirim, Keputusan Pembelian, Erigo, Shopee